Sistem Pengolahan Data Di Lingkungan Pemerintahan - Safitri, Yudiantarti (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2009)
Today we lived in the era of technology there for our government institutions must utilize these technologies. Technology can make our work more efficient and effective. Though good human resources are irreplaceable, suitable technologies are also invaluable in order to complete our work quickly and accurately. One area that requires accuracy is data processing of personal information, finance information and social information.these three areas are very important in making decisions in management, this is why when processing data it must be done accurately.